Are foreign-owned firms different? Comparison of employment volatility and elasticity of labour demand - Jaanika Meriküll; Tairi R\~o\~om (European Central Bank (ECB), 2014)
This paper analyses differences in employment volatility in foreign-owned and domestic companies using firm-level data from 24 European countries. The presence of foreign-owned companies may lead to higher employment volatility because subsidiaries of multinational companies react more sensitively to changes in labour demand in host countries or because they are more exposed to external shocks. We assess the conditional employment volatility of firms with foreign and domestic owners using propensity score matching and find that it is higher in foreign-owned firms in about half of the countries that our study covers. In addition, we explore how and why labour demand elasticity differs between these two groups of companies. Our estimations indicate that labour demand can be either more or less elastic in subsidiaries of foreign-owned multinationals than in domestic enterprises, depending on the institutional environments of their home and host countries.
Keywords: F23; J23; J51; 330; employment volatility; European Union; foreign direct investment; Labour Demand; Labour Market Institutions